The Influence of Structural Resources on the Performance of Micro-Businesses in the Agrotourism Sector with Human Capital as a Moderator - Adi Indradi Wazdi; Nur'aeni Nur'aeni; Setiawan Setiawan; Asep Abdul Halim (Fakultas Ekonomi dan Bisnis Islam, 2026)
This study examines the influence of structural resources on the performance of micro-enterprises in the agrotourism sector, with human capital as a moderating variable. Agrotourism, which combines the agricultural and tourism sectors, has significant potential for boosting the local economy. However, in some areas, such as Ciwidey and Lembang, its development is still suboptimal due to limited infrastructure, a lack of innovation, and suboptimal synergy between stakeholders. This study uses a quantitative approach with an associative method to analyze the relationship between government promotion, brand identification, and financial access on the performance of agrotourism micro-enterprises. Data were collected through a Likert-scale questionnaire administered to micro-enterprises in this sector. Data analysis was conducted using structural equation modeling (SEM-PLS) to test the direct effect and moderating role of human capital. The results showed that government promotion had no significant effect on micro-enterprise performance. Conversely, brand identification and financial access had a significant positive effect on business performance. The moderating role of human capital showed mixed results: the relationship between government promotion and performance was insignificant, the relationship between brand identification and performance was weakened by human capital moderation, while the relationship between financial access and performance was strengthened by human capital.